K. D. Balmont in the Reception of A. A. Izmailov - ALEKSANDROV, ALEKSANDR; ALEKSANDROVA, ELMIRA (Bulletin of Yerevan University H: Russian Philology, 2021)
This article is based on A. Izmajlov’s and K. Balmont’s correspondence (1907-1915). Izmailov is known as a gifted parodist of modernist literature. He reacted very negatively to the first experience of the emerging trends. Over time, his views on literary modernists products have undergone a certain evolution. This article provides an overview of critical reviews of the Balmont’s poetry. It allows to correct the widespread belief about Izmailov as an irreconcilable opponent of modernist literature.
Keywords: Balmont, Izmailov, «Birzhevye vedomosti», correspondence, critical article